Features of phagocytosis function in children of preschool age depending on the incidence of acute respiratory diseases - L.S. Ovcharenko; O.V. Tymoshyna; A.O. Vertehel; T.G. Andrienko; I.V. Samokhin; O.V. Kryazhev (Zaslavsky O.Yu., 2021)
Background. Recently, with the emergence of new pathogenic viruses' variants, attention is drawn to the functioning status of innate immunity components, which are able to neutralize unknown microorganisms at the early stages of infection. Therefore, the study of phagocytosis disorders in children with respiratory recurrent infectious diseases will supply the scientific data on the processes of age-dependent formation of antimicrobial protection. The purpose: to improve the diagnosis of innate immune disorders in preschool children with respiratory recurrent infectious on the background of new data on phagocytosis parameters. Materials and methods. Sixty children aged from 2 to 5 years were observed. Two groups were formed: 1) children with respiratory tract acute infectious more than 6 times per year (n = 30); 2) children with respiratory acute infectious 6 or fewer times per year (n = 30). Results. The children of group 1 presented with statistically significantly increased cases of low phagocytic counts (by 60.0 %, p < 0.05), phagocytic index (by 56.0 %, p < 0.05), index of phagocytosis completeness (70.0 %, p < 0.05), neutrophil phagocytic activity stimulated by Staphylococcus (50.0 %, p < 0.05) and high rates of spontaneous neutrophil phagocytic activity (43.3 %, p < 0.05), increased serum level of interleukin-1β (46.7 %, p < 0 05), interleukin-6 (43.3 %, p < 0.05), interleukin-10 (by 30.0 %, p < 0.05), TNF (by 46.7 %, p < 0.05). Conclusions. In children aged 2-5 years with respiratory acute infectious diseases more than 6 times per year, phagocytic dysfunction was established. It is manifested itself in a decrease of phagocytosis absorption and stimulated metabolic activity on the background of increased pro- and anti-inflammatory cytokines serum level, ie cytokine imbalance.